Determinants of brain-derived neurotrophic factor (BDNF) in umbilical cord and maternal serum. (January 2016) - Flöck, A.; Weber, S.K.; Ferrari, N.; Fietz, C.; Graf, C.; Fimmers, R.; Gembruch, U.; Merz, W.M.
Highlights: The origin of circulating maternal and umbilical cord (UC) BDNF remains unresolved. BDNF traffic between mother and fetus is unlikely. Mode of delivery and gestational age are determinants of UC-BDNF. Gestational age is the only determinant of maternal BDNF concentration. BDNF may be involved in the neurohormonal cascade of parturition. Abstract: Objective: Brain-derived neurotrophic factor (BDNF) plays a fundamental role in brain development; additionally, it is involved in various aspects of cerebral function, including neurodegenerative and psychiatric diseases. Involvement of BDNF in parturition has not been investigated. The aim of our study was to analyze determinants of umbilical cord BDNF (UC-BDNF) concentrations of healthy, term newborns and their respective mothers. Methods: This cross-sectional prospective study was performed at a tertiary referral center. Maternal venous blood samples were taken on admission to labor ward; newborn venous blood samples were drawn from the umbilical cord (UC), before delivery of the placenta. Analysis was performed with a commercially available immunoassay. Univariate analyses and stepwise multivariate regression models were applied. Results: 120 patients were recruited. UC-BDNF levels were lower than maternal serum concentrations (median 641 ng/mL, IQR 506 vs. median 780 ng/mL, IQR 602). Correlation between UC- and maternal BDNF was low ( R  = 0.251, p  = 0.01). In univariate analysis, mode of delivery (MoD), gestational age (GA), body mass index at delivery, and gestational diabetes were determinants of UC-BDNF (MoD and smoking for maternal BDNF, respectively). Stepwise multivariate regression analysis revealed a model with MoD and GA as determinants for UC-BDNF (MoD for maternal BDNF). Conclusions: MoD and GA at delivery are determinants of circulating BDNF in the mother and newborn. We hypothesize that BDNF, like other neuroendocrine factors, is involved in the neuroendocrine cascade of delivery. Timing and mode of delivery may exert BDNF-induced effects on the cerebral function of newborns and their mothers.